50th anniversary of the youth revolution: versions, results, lessons - Zapesotsky, Alexander S. (Journal of the Belarusian State University. Sociology, 2019)
The article deals with the prerequisites, stages and results of the youth revolution. The most important socio-psychological factors and forms of youth protest expression are described. The fundamental contradiction between the humanistic pathos of the revolution and the huge social risks in relation to the bearing structures of the society is analyzed. The youth revolution of 1968 is considered as a global cultural project, denying the «old» culture. The postmodern and neo-liberal model of capitalism is justified as the main results of the «youth revolution».
Keywords: youth revolution; social protest; anti-bourgeois pathos; postmodern